Fool moon ebook - Butcher, Jim (The Dresden Files, 2001)
“One of the most enjoyable marriages of the fantasy and mystery genres on the shelves,”( Cinescape ) the Dresden Files have become synonymous with action-packed urban fantasy and nonstop fun. Fool Moon continues the adventures of Jim Butcher’s most famous—and infamous—reluctant hero…   You’d think there’d be a little more action for the only professional wizard listed in the Chicago phone book. But lately, Harry Dresden hasn’t been able to dredge up any kind of work: magical, mundane, or menial.   Just when it looks like he can’t afford his next meal, a murder comes along that requires his particular brand of supernatural expertise. There’s a brutally mutilated corpse, and monstrous animal markings at the scene. Not to mention that the killing took place on the night of a full moon. Harry knows exactly where this case is headed. Take three guesses—and the first two don’t count...